(untitled) - Raes, Dirk ([ Thailand ], 1996)
This book introduction about climate, evapotranspiration, rainfall, irrigation requirement, pant-soil-water system, irrigation scheduling.
Keywords: Irrigation,Drainage,Tưới tiêu,Thủy lợi